Tumor Microenvironment in Acute Myeloid Leukemia: Adjusting Niches - Menter, Thomas; Tzankov, Alexandar (Frontiers in Immunology, 2022)
Acute myeloid leukemias (AML) comprise a wide array of different entities, which have in common a rapid expansion of myeloid blast cells leading to displacement of normal hematopoietic cells and also disruption of the microenvironment in the bone marrow niches. Based on an insight into the complex cellular interactions in the bone marrow niches in non-neoplastic conditions in general, this review delineates the complex relationship between leukemic cells and reactive cells of the tumor microenvironment (TME) in AML. A special focus is directed on niche cells and various T-cell subsets as these also provide a potential therapeutic rationale considering e.g. immunomodulation. The TME of AML on the one hand plays a vital role for sustaining and promoting leukemogenesis but - on the other hand - it also has adverse effects on abnormal blasts developing into overt leukemia hindering their proliferation and potentially removing such cells. Thus, leukemic cells need to and develop strategies in order to manipulate the TME. Interference with those strategies might be of particular therapeutic potential since mechanisms of resistance related to tumor cell plasticity do not apply to it.